Ecological Limits and Hierarchical Power - Blair Fix; Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2019)
Nowadays, it is commonplace to claim that the economy overuses our limited material and energy resources and that this overuse threatens both human society and the biosphere. Other than anti-science cranks, the only ones who seem to deny this claim are mainstream economists. In our view, though, this conventional condemnation of the economy is somewhat misleading. As we see it, the root of our ecological problems lies not in the `economy', but in the hierarchical power structure of capitalism.
Keywords: P18; P48; P16; Q01; 330; energy; hierarchy; power; sustainability